BCOR-CCNB3 rearranged sarcoma arising in neck misdiagnosed as thyroid cancer: A case report. (September 2021) - Tan, Li-Cheng; Yu, Peng-Cheng; Wang, Jian; Zhou, Xiao-Yan; Ji, Qing-Hai; Wang, Yu-Long
Abstract: BCOR -rearranged sarcoma is the third common subtype of undifferentiated small round cell sarcoma and was first recognized in 2012 from bone sarcoma with a similar morphological manifestation with undifferentiated round cell but totally different molecular hallmark from Ewing sarcoma. Primary BCOR -rearranged sarcomas were mostly found in bone and soft tissue and were sporadically reported in viscera involving kidney, which add difficulties in differential diagnosis. Here we present a 21 years old male patient with BCOR-CCNB3 in neck, which first diagnosed as thyroid cancer.